Evolution of population concerns: Reflections from the Asian and Pacific Population Conferences - Mercedes B. Concepcion (Asia-Pacific Population Journal, 2003)
The United Nations Seminar on Population in Asia and the Far East, held at Bandung, Indonesia, in 1955, focused attention on increasing population trends within the region covered by the Economic Commission for Asia and the Far East (ECAFE). The Seminar realized that the current rising population growth rates largely negated or probably even retarded the effects of national socio-economicprogrammes that provided an environment conducive to lowering birth rates. Interest in the region’s population gains was further stimulated by the establishment of the Demographic Training and Research Centre at Bombay, India, jointly operated by the United Nations and the Government of India. At the Centre’s inaugural conference it was suggested that the United Nations convene a regional conference on population. That proposal was taken up by the Commission in its resolution 28 (XV) of 13 March 1959 requesting the secretariat to organize an Asian population conference where experts could examine the major problems of planning for economic and social development arising from current and prospective trends in population growth, composition and geographic distribution. Consequently, in 1963, the First Asian Population Conference (APC) was held at New Delhi, with the Government of India providing host facilities. APC was established as a statutory organ of the Commission to be convened every 10 years to consider all aspects of population questions and, of their impact on economic and social development as mandated in Commission resolution 74 (XXIII) of 17 April 1967.